2020
DOI: 10.5194/acp-20-3415-2020
|View full text |Cite
|
Sign up to set email alerts
|

Synoptic-scale controls of fog and low-cloud variability in the Namib Desert

Abstract: Abstract. Fog is a defining characteristic of the climate of the Namib Desert, and its water and nutrient input are important for local ecosystems. In part due to sparse observation data, the local mechanisms that lead to fog occurrence in the Namib are not yet fully understood, and to date, potential synoptic-scale controls have not been investigated. In this study, a recently established 14-year data set of satellite observations of fog and low clouds in the central Namib is analyzed in conjunction with rean… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 76 publications
(134 reference statements)
1
14
0
Order By: Relevance
“…A study found that the formation of advection fog is attributed to. Synoptic-scale circulation (South Atlantic high and lower mean sea level pressure on land) circulation in Namib desert causes alteration in the moisture transport and intensified cooling of the marine boundary layer, helping in the formation of sustenance of advection fog (Andersen et al 2020 ). Similarly, Koran Western peninsula experiences fog when there is the formation of a high-pressure zone in the Yellow sea, during night time the moisture-laden south-westerly winds flow towards the land where it meets offshore land breeze and Katabatic easterly winds, together with nocturnal cooling the air becomes saturated leading to the formation of advection fog near the coast (Choi and Speer 2006 ).…”
Section: Factors Influencing Fog Formationmentioning
confidence: 99%
“…A study found that the formation of advection fog is attributed to. Synoptic-scale circulation (South Atlantic high and lower mean sea level pressure on land) circulation in Namib desert causes alteration in the moisture transport and intensified cooling of the marine boundary layer, helping in the formation of sustenance of advection fog (Andersen et al 2020 ). Similarly, Koran Western peninsula experiences fog when there is the formation of a high-pressure zone in the Yellow sea, during night time the moisture-laden south-westerly winds flow towards the land where it meets offshore land breeze and Katabatic easterly winds, together with nocturnal cooling the air becomes saturated leading to the formation of advection fog near the coast (Choi and Speer 2006 ).…”
Section: Factors Influencing Fog Formationmentioning
confidence: 99%
“…Therefore, the diurnal cycle of the coastal circulation is likely a main driver of the observed patterns in FLS formation and dissipation times at the Mediterranean coast. At the Atlantic coast of northern Spain, blocking of FLS by the Cantabrian mountains (Egli et al ., 2017) and upwelling (Alvarez et al ., 2010) might be important for FLS formation, as the latter plays an important role in other FLS‐prone regions such as at the southwestern African coast (Olivier and Stockton, 1989; Cermak, 2012; Andersen et al ., 2020). Close to the French Atlantic coast over the Landes forest south of 45°N, FLS forms earlier over the forest (around midnight) than over its surroundings (FLS formation in the morning), particularly in spring and summer.…”
Section: Discussionmentioning
confidence: 99%
“…9g). This circulation pattern advects moist, warm air along the coast of Namibia, encouraging an inland fog (Andersen et al, 2020). Perhaps this produces enough precipitation to reduce N d near the shore, although that remains speculation.…”
Section: October: Increased Cloud Cover On Smokier Daysmentioning
confidence: 98%